Taurine Alleviated the Negative Effects of an Oxidized Lipid Diet on Growth Performance, Antioxidant Properties, and Muscle Quality of the Common Carp (Cyprinus carpio L.) - Dan Liu; Jiali Mi; Xiao Yan; Chaobin Qin; Junli Wang; Guoxing Nie (Aquaculture Nutrition)
In the present study, we conducted a 10-week culture experiment to investigate the effects of taurine on the growth performance, antioxidant properties, and muscle quality of the common carp fed an oxidized lipid diet. There were five experimental groups with three replicates each. Based on the fresh fish oil group (FO), equal amounts of oxidized fish oil (with a thiobarbituric acid-reactive substances value of 49.57 ± 2.34 mg/kg) and 0 g/kg (OFO), 4 g/kg (OT4), 8 g/kg (OT8), and 12 g/kg (OT12) taurine were added to the diet, while the same composition ratio was maintained by changing the microcrystalline cellulose content. Compared to the FO group, the feed conversion ratio, weight gain rate, muscle crude lipid, and n-3/n-6 polyunsaturated fatty acids (PUFA) ratio were significantly lower in the group OFO (P<0.05). In addition, compared to the FO group, OFO fish showed an increased content of malondialdehyde and protein carbonylation and decreased hardness, brightness, pH, superoxide dismutase, and catalase levels in the muscle (P<0.05). Notably, the growth index significantly improved in the OT4 group compared to that in the OFO group (P<0.05). In addition, dietary taurine increased the crude lipid content, n-3/n-6 PUFA, antioxidant capacity, hardness, springiness, brightness, pH, and collagen content in the muscle compared with OFO fish (P<0.05). Moreover, taurine supplementation significantly reduced myofiber diameter and increased myofiber density (P<0.05) and enhanced the expression levels of paired box 7 (pax7), myogenic factor 5 (myf5), myogenic differentiation antigen (myod), and myogenic regulatory factor 4 (mrf4) compared with that of the OFO group (P<0.05). Considering growth performance and muscle quality, the optimal supplemental levels of taurine in the oxidized lipid diet were 4 g/kg and 6.84–7.70 g/kg, respectively.